Pengaruh Perbandingan Terigu dan Tepung Sorgum Putih Terfermentasi Terhadap Karakteristik Roti Manis - Tiffany, Cassey; Indri Hapsari Arihantana, Ni Made; Darmayanti, Luh Putu Trisna (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
This study was aimed to determine the effect comparison of wheat and fermented white sorghum flour on the characteristics of sweet bread and to determine the right ratio of wheat and fermented white sorghum flour to produce sweet bread with the best characteristics. This study used a Completely Randomized Design with treatment ratio of wheat flour and fermented white sorghum flour that consists of 6 levels namely; 100%:0%, 90%:10%, 80%:20%, 70%:30%, 60%:40%, and 50%:50%. The treatment was repeated 3 times to produce 18 experimental units. The data obtained will be analyzed using analysis of variance, if the treatment had a significant effect, it will be continued with the Duncan's Multiple Range Test (DMRT) test. The results showed that the ratio between wheat flour and fermented white sorghum flour had a significant effect on moisture content, ash content, crude fiber content, development power, pore uniformity, bread hardness, hedonic test (color, aroma, texture, taste, and overall acceptance), and scoring test (colors and texture) for the sweet bread. The ratio of 70% wheat and 30% fermented white sorghum flour had the best characteristics of sweet bread with moisture content 22.02%, ash content 1.21%, crude fiber content 4.24%, development power 170.41%, pore uniformity 79.67, bread hardness 7.06 N, with sensory characteristics of color browny-yellow was liked, the texture was soft enough and was liked, and for aroma, taste, overall acceptance was liked.